Communs paysagers et devenirs éoliens opposés - Alain Nadaï; Olivier Labussière (Projets de Paysage)
This article starts with the opposition to a wind farm project which led to conflict in a village in Seine-et-Marne (France). It follows the emergence and the gradual structuring of the trajectories of the opposing parties by exploring the roles and different opposing projects for shared landscapes. At the intersection between these conflicting changes and projected landscapes, the analysis sheds light on the reasons why institutions in France fail to establish the connection between heterogeneous shared landscapes to support the emergence of joint wind farm projects.